Trans/figuracje nowoczesności? Spory o twórczość Marii Komornickiej-Piotra Odmieńca Własta - Chmurski, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article is a reflection of how the work by Maria Komornicka (pen name Piotr Odmieniec Włast) was perceived in the past two decades on the basis of an analysis of a monograph by Edward Boniecki (1996), Izabela Filipiak (2006) and Brigitta Helbig-Mischewski (2010) in the context of changes in the interpretation of modern Polish literature. In the article, attention is drawn to three groups of issues which can only be identified on the basis of contemporary perception, incomplete as it is, due to the fact that all the works of Komornicka have not been published. The forms and meaning of broadly defined autobiographical writing has been re-defined, while Polish and regional literary modernism has been revised together with the involvement of literary researchers in the subject of their analyses. The author of the article suggests a schematic differentiation between updating, prospective and retrospective strategies in Komornicka’s work and a reflection on the indirect involvement in social and cultural discourses and discussions developed by contemporary researchers into Komornicka’s work.